Liberal Preoperative Fasting in Adults Undergoing Elective Surgery: A Scoping Review Protocol - Haoyue Gan; Hangcheng Liu; Huaping Huang; Mei He (Anesthesiology Research and Practice)
Background. Prolonged fasting before surgery has negative effects on the physiology and psychology of patients. Preoperative liberal fasting proposes that patients can drink clear liquids before entering the operating theater, challenging the guideline strategy of a two-hour preoperative liquid fast for adults. In recent years, there have been an increasing number of studies on liberal preoperative fasting in adults. However, currently there is no consensus on the safe amount of fluid consumed, adverse effects, or benefits of this new policy. Objective. This scoping review protocol will map the existing evidence of liberal preoperative fasting in adults undergoing elective surgery for clinical practice, to summarize more scientific evidence to healthcare professionals when providing perioperative care. Methods and Analysis. The methodology will follow the six steps of the Arksey and O’Malley methodological framework and be guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review. A comprehensive search of six databases will be performed from their inception to 31 May 2023 to identify suitable English studies. Two trained investigators will independently screen and extract the data, and any disagreements will be judged by a third investigator. The results of the study will be presented as graphs or tables. Ethics and Dissemination. This scoping review only examines literature in the database, without reference to human or animal studies, and therefore does not require ethical approval. The findings of this scoping review will be published in peer-reviewed journals or presented at conferences. The Registration Number. This scoping review has been registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/PMW7C).